Persistent, Extensive Channelized Drainage Modeled Beneath Thwaites Glacier, West Antarctica - Hager, Alexander O.; Hoffman, Matthew J.; Price, Stephen F.; Schroeder, Dustin M. (Zenodo, 2021)
Model code and results, analysis scripts, and radar specularity content data used in "Persistent, Extensive Channelized Drainage Modeled BeneathThwaites Glacier, West Antarctica", submitted to the Cryosphere, fall 2021.